CRM adoption factors in the gaming industry - Faganel, Armand (Array, 2020)
The aim of this paper is to evaluate critical success factors and investigate the benefits that might be gained by adopting Customer Relationship Management (CRM) in the gaming industry from the perspective of individuals involved in the process of adopting the CRM. A total number of 109 casinos’ managers from all over the world have been surveyed about the factors’ importance for the CRM adoption. Based on the multiple regression and ANOVA analysis, an estimated function of the influence of the most important umbrella factors – human, project and technological, for the success of CRM project in a company has been formulated. The highest rated elements in successful cases of CRM adoption are almost entirely bound to human factor. CRM systems are estimated to evolve further into a direction of individual customer experience management and become more and more intelligent, integrated and data-driven.